Genome-wide meta-analysis of Psoriatic Arthritis Identifies Susceptibility Locus at REL - Ellinghaus, Eva (2011)
Psoriatic arthritis (PsA) is a chronic inflammatory musculoskeletal disease affecting up to 30% of psoriasis vulgaris (PsV) cases and approximately 0.25% to 1% of the general population. To identify common susceptibility loci, we performed a meta-analysis of three imputed genome-wide association studies (GWAS) on psoriasis, stratified for PsA. A total of 1,160,703 SNPs were analyzed in the discovery set consisting of 535 PsA cases and 3,432 controls from Germany, the United States and Canada. We followed up two SNPs in 1,931 PsA cases and 6,785 controls comprising six independent replication panels from Germany, Estonia, the United States and Canada. In the combined analysis, a genome-wide significant association was detected at 2p16 near the REL locus encoding c-Rel (rs13017599, P=1.18×10−8, OR=1.27, 95% CI=1.18–1.35). The rs13017599 polymorphism is known to associate with rheumatoid arthritis (RA), and another SNP near REL (rs702873) was recently implicated in PsV susceptibility. However, conditional analysis indicated that rs13017599, rather than rs702873, accounts for the PsA association at REL. We hypothesize that c-Rel, as a member of the Rel/NF-κB family, is associated with PsA in the context of disease pathways that involve other identified PsA and PsV susceptibility genes including TNIP1, TNFAIP3 and NFκBIA.